A new Ag‐based photocatalyst for efficient degradation of antibiotic nitrofurantoin - Liu, Yichen; Zhou, Changxin; Xiang, Ruifang; Xiong, Dingqi; Li, Duqingcuo; Qin, Tianrui; Dong, Xiuyan; Muddassir, Mohd; Pan, Ying (Applied organometallic chemistry, 2024)
In this paper, a new 0D Ag(I)‐based coordination polymer [Ag2(dib)(H2L)2](1) is proposed as a photocatalyst for the photocatalytic degradation of nitrofurantoin (NFT) under ultraviolet irradiation. The catalytic 1 was analyzed by various methods such as PXRD, SEM, FT‐IR, TGA, UV–vis, DRS, and electrochemical tests. The experimental result shows that 1 is an n‐type semiconductor, which can effectively catalyze the photodegradation of NFT under ultraviolet irradiation. Under the optimal reaction conditions, the photodegradation rate of NFT was 97.95% within 60 min when the concentration of NFT was 30 ppm. The experiment of free radical capture shows that O2˙− is the main active substance for photodecomposition, and the possible mechanism of 1 catalytic degradation of NFT is proposed. This research will lay the foundation for Ag(I)‐based coordination polymers in the field of antibiotic photocatalytic degradation. A new 0D Ag(I)‐based coordination polymer [Ag2(dib)(H2L)2](1) photocatalyzed NFT degradation rate of 97.95%. O2˙− is the main active substance for photodecomposition, and the possible mechanism of 1 catalytic degradation of NFT is proposed.